Relationship between Breastfeeding Position and Events Chafed Nipples - Mundari, Risa; Ayu Ningsih, Dewi; Lidia Sari, Nirma; Fatriani, Rully (Jurnal MIDPRO, 2023)
Problems during breastfeeding are caused by breastfeeding mothers' low knowledge about the breastfeeding process. The aim of the study to provide midwifery care to postpartum mothers on the 14th day by providing the correct breastfeeding position at PMB NH Bandar Lampung City. The design of educational needs about research used is descriptive with a case study approach. This case study research was conducted from April 4 2023 to April 5 2023. The subject of this research was Mrs. T Postpartum day 14.  Implementation of continuing midwifery care for Mrs. T is carried out in accordance with midwifery service standards. The midwifery care provided by the researchers was the correct breastfeeding technique or the correct breastfeeding position to prevent chafed nipples. From the study it was found that postpartum mothers experience sore nipple discomfort, the authors have made a diagnosis and made a plan, Mrs. T was given management according to the mother's complaints, namely by treating chafed nipples and breastfeeding techniques properly and correctly. This is in accordance with the needs of the mother and midwifery care standards. Care is evaluated and documented in accordance with midwifery care for postpartum mothers using the SOAP method according to Varney's mindset. It is recommended for PMB to be able to prepare health education media such as leaflets, posters related to the discomfort of chafed nipples in postpartum mothers, so that patients